Pengaruh Kepemimpinan Transformasional, Budaya Organisasi Terhadap Komitmen Organisasi dan Implikasinya Pada Kinerja Karyawan di PT. Kredo Keramindo Sejahtera Pekanbaru - Litra Diantara; Desmawati Desmawati; Tamrin Tamrin (Komunitas Dosen Indonesia, 2022)
This study aims to examine the influence of transformational leadership and organizational culture on organizational commitment and the implications for employee performance at PT. Credo Keramindo Prosperous Pekanbaru. The sample specified in this study is as many as 112 employees. The data analysis method uses Structural Equation Modeling (SEM). The results showed that transformational leadership has a significant effect on organizational commitment, organizational culture has a significant effect on organizational commitment, transformational leadership has a significant effect on performance, organizational culture has a significant effect on performance, organizational commitment has a significant effect on performance, transformational leadership has a significant effect on performance through organizational commitment and Organizational culture has a significant effect on performance through organizational commitment